The Role of Digital Payment in Promoting MSME Financial Inclusion: Implications for Innovation-Based Community Service Activities - Irwan Moridu; Adrian Polim; Nurcahya Hartaty Posumah; Debiyanti Kune; Fitriani (PT. LITERASI SAINS NUSANTARA, 2026)
The transformation of digital technology has driven significant changes in payment systems, contributing to the expansion of financial inclusion, particularly for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of digital payment in promoting MSME financial inclusion and its implications for innovation-based community service activities, while also enriching the literature on community engagement within the digital economy context. The method employed is a literature review using a qualitative approach through descriptive analysis of sources obtained from Google Scholar and various credible websites spanning the period 1964–2026. From an initial pool of 50 identified articles, a rigorous selection process resulted in 34 relevant articles for further analysis. The findings indicate that digital payment plays a significant role in enhancing MSMEs’ access to formal financial services, strengthening transaction transparency, and supporting the creation of financial track records that contribute to improved access to financing. The discussion also reveals that successful technology adoption is influenced by factors such as digital literacy, infrastructure availability, and trust in the system. Innovation-based community service activities play a strategic role in bridging these gaps through contextual education, training, and mentoring.